BackPack Track : An android mobile application for backpackers' travel itineraries and budget tracking / Muhammad Afif Zafri Khuzairi - Khuzairi, Muhammad Afif Zafri (2019)
Backpacking has become a popular travelling method in recent years because it focuses on minimising budget spending during travelling. To minimize the budget, trip itinerary planning is important. However, it is quite difficult in planning for a travel itinerary if there is insufficient information. Currently, backpackers rely on social media platforms for finding the information, but this information is usually incomplete and not structured properly. Based on the study of existing applications, it was found that these applications lack important features such as to record and track budget spending and to browse the itineraries shared by other users. Therefore, BackPack Track has been developed in order to solve these problems and fills in the gaps of existing applications. With BackPack Track, users are able to record and share their own trip itineraries. This itinerary consist of the country visited, the activities and places visited where the apps will store the GPS locations, the photographs, and most importantly is the budget spends for each activities. The application will help users to view the overall budget spending for an itinerary. Users are also able to browse itineraries shared by other users. This project has been successfully developed by using Waterfall Methodology. The project consists of a Laravel Web Based Application for the Admin Web Panel and Web API and an Android mobile application which implements Location Based Service (LBS) using Google Maps APL For future works, real-time push notifications and a chatting feature are recommended to be integrated with this application so that BackPack Track can serve as a complete trip planning platform for backpackers. In addition, this project should also become a cross-platform application so that the user base can be increased - hence reaching a wider acceptance among the backpackers community.